Nonverbal techniques in social network language - Kurmanbekova З.Р.; Makulova Л.Т.; Sarsembayeva М.К. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The paper highlights emoticons, which are an important aspect of social networking communication. The definition of emoticons was offered in this paper, which was based on scientific research. Emoticons help to uncover and comprehend the goal of the netizen conversation. Nowadays, the fast penetration of social networks into our daily lives has expanded the quantity of nonverbal techniques in internet communication language and modified them graphically and by content. The advent of emoticons, visual and creole as a way of marking, emoticons and stickers, demotivators, internet memes, and characters such as comics reflect the internet’s transition to nonverbal communication. The paper’s scientific novelty is the first consideration of nonverbal information as the primary technique of transferring moods and emotions in the process of internet communication in Kazakh language. For the first time, features such as emoticons (emojis), demotivators and advisors are incorporated into Kazakh language resources.